OPTIMALISASI PERAN DPRD DALAM MELAKSANAKAN FUNGSI PENGAWASAN TERHADAP PEMERINTAH KOTA MAKASSAR: Telaah SIyasah Syar’iyyah) - Amal, Amalia Sururiah; Darussalam; Hasan, Hamzah (Siyasatuna: Jurnal Ilmiah Mahasiswa Siyasah Syar’iyyah, 2025)
The purpose of this research was to find out how the role of Makassar City’s DPRD in carrying out the supervisory function of the Makassar City Government and find out what obstacles are faced by Makassar City’s DPRD in supervising the Makassar City Government. As for the method used in this research is field research with an empirical juridical research approach and syar’i normative. The result showed that optimizing the role of DPRD in carrying out the supervisory function of the Makassar City Goverment running optimally although there all still some obstacles faced by DPRD in carrying out the supervisory function. The obstacles faced by Makassar City’s DPRD in carrying out the supervisory function are : The people was unable to cooperate, Covid-19 pandemic, the company was unable to cooperate and people still fear convey their opinions and rights to the government. The Siyasah Syar’iyyah concept views that accountability for something that has been mandated was a basic thing whose substance demands professionalism and accountability.